Early Oxidative Transformations During the Biosynthesis of Terrein and Related Natural Products. Issue 46 (24th June 2021) - Kahlert, Lukas; Bernardi, Darlon; Hauser, Maurice; Ióca, Laura P.; Berlinck, Roberto G. S.; Skellam, Elizabeth J.; Cox, Russell J.
Abstract: The mycotoxin terrein is derived from the C10 ‐precursor 6‐hydroxymellein (6‐HM) via an oxidative ring contraction. Although the corresponding biosynthetic gene cluster (BGC) has been identified, details of the enzymatic oxidative transformations are lacking. Combining heterologous expression and in vitro studies we show that the flavin‐dependent monooxygenase (FMO) TerC catalyzes the initial oxidative decarboxylation of 6‐HM. The reactive intermediate is further hydroxylated by the second FMO TerD to yield a highly oxygenated aromatic species, but further reconstitution of the pathway was hampered. A related BGC was identified in the marine‐derived Roussoella sp . DLM33 and confirmed by heterologous expression. These studies demonstrate that the biosynthetic pathways of terrein and related (polychlorinated) congeners diverge after oxidative decarboxylation of the lactone precursor that is catalyzed by a conserved FMO and further indicate that early dehydration of the side chain is an essential step. Abstract : Heterologous expression of two related biosynthetic gene clusters from Aspergillus terreus and Roussoella sp. DLM33 confirmed a conserved flavin‐dependent monooxygenase that initiates the oxidative decarboxylation of the key intermediate (dichloro‐) 6‐hydroxymellein. Further in vitro studies imply that both pathways diverge after this initial oxidation, whereas additional dehydration appears essential for downstream processing.